ANALISIS AKAD IJARAH MUNTAHIYA BITTAMLIK DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Munif, Nasrulloh Ali (IAIN Tulungagung, 2016)
The fast growing of shariah financial industry has forced thepractioners and academist of shariah banking to be more innovativeto meet the demand. One of the innovation is the settlement of newagreement called Ijarah Al Muntahiya bit Tamlik (financial leasingwith purchase). This agreement is a hybrid transaction which combinesleasing and ownership in the end of the leasing. This innovation hasturned to give some benefit and advantages. However, the legal basisof its operation, both from the Islamic perspective and the Indonesianpositive law, is being questioned. Anyway, from the perspective ofIslamic law Ijarah Muntahiya Bittamlik has fulfilled the requirementand three criteria of legal transaction even though there is a differentopinion saying that it may belong to the join transaction (murakab)which is forbidden by the Prophet. The majority of Islamic juristscome to their common agreement that Ijarah Muntahiya Bittamlikis allowed. From the perspective of Indonesian positive law, IjarahMuntahiya Bittamlik belongs to anonymous agreement (article 1319)which emerges due to the freedom to settle an agreement (article1338) and Ijarah Muntahiya Bittamlik has fulfilled the criteria of alegal transaction (article 1320) and the components of a transaction.The legal impact of Ijarah Muntahiya Bittamlik is the rights and theresponsibilities of the parties involved.Kata kunci: Ijarah Muntahiya Bittamlik, Hukum Islam, Hukum positif